Integrating youth mental health into cash transfer programmes in response to the COVID-19 crisis in low-income and middle-income countries. (April 2021) - Bauer, Annette; Garman, Emily; McDaid, David; Avendano, Mauricio; Hessel, Philipp; Díaz, Yadira; Araya, Ricardo; Lund, Crick; Malvasi, Paulo; Matijasevich, Alicia; Park, A-La; Paula, Cristiane Silvestre; et al.
Summary: Social protection measures can play an important part in securing livelihoods and in mitigating short-term and long-term economic, social, and mental health impacts of the COVID-19 pandemic. In particular, cash transfer programmes are currently being adapted or expanded in various low-income and middle-income countries to support individuals and families during the pandemic. We argue that the current crisis offers an opportunity for these programmes to focus on susceptible young people (aged 15–24 years), including those with mental health conditions. Young people living in poverty and with mental health problems are at particular risk of experiencing adverse health, wellbeing, and employment outcomes with long-term consequences. They are also at risk of developing mental health conditions during this pandemic. To support this population, cash transfer programmes should not only address urgent needs around food security and survival but expand their focus to address longer-term mental health impacts of pandemics and economic crises. Such an approach could help support young people's future life chances and break the vicious cycle between mental illness and poverty that spirals many young people into both socioeconomic and mental health disadvantage.